Linear and nonlinear monetary approaches to the exchange rate of the Philippines peso-Japanese yen - Liew, Venus Khim-Sen (Economics Bulletin, 2009)
This study provides evidence of nonlinear long-run relationship between peso-yen exchange rate and its monetary determinants implied by the reduced-form flexible-price monetary model for the Philippines, using Breitung's (2001) nonlinear cointegration testing procedures. The existence of such relationship is probably resulted from the strong and consistent bilateral trade relationship between the Philippines and Japan. Results from various monetary restrictions tests suggest that other forms of the related monetary model are not suitable in the determination of the peso-yen exchange rate.